2001
DOI: 10.1007/s11938-001-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Benign neoplasms of the liver

Abstract: Tumors of the liver often are discovered incidentally in asymptomatic individuals during diagnostic imaging or exploratory laparotomy performed for alternative reasons. Hemangiomas are the most common benign liver tumors, followed in prevalence by focal nodular hyperplasia (FNH); other benign tumors are rare. The growth and development of hemangiomas, FNH, and hepatic adenomas especially, have been linked to hormonal (eg, estrogen) stimulation. Differentiating between benign and malignant neoplasms of the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Etiology of hemangiomas is not well defined, but the affects of female sex hormones are debated. Hepatic hemangioma is seen 5-6 times more frequently in women than men in adults (Ochsner and Halpert 1958;Porayko and Choudhray 2001;Reddy et al 2001). In addition, female patients often develop larger and multiple tumors than men (Reddy et al 2001), and rapid enlargement of hemangioma during pregnancy are also reported (Saegusa et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiology of hemangiomas is not well defined, but the affects of female sex hormones are debated. Hepatic hemangioma is seen 5-6 times more frequently in women than men in adults (Ochsner and Halpert 1958;Porayko and Choudhray 2001;Reddy et al 2001). In addition, female patients often develop larger and multiple tumors than men (Reddy et al 2001), and rapid enlargement of hemangioma during pregnancy are also reported (Saegusa et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of the liver hemangioma is approximately 2% in population with the predilection of female sex (Ochsner and Halpert 1958;Porayko and Choudhray 2001;Reddy et al 2001). It is usually solitary but can be multiple in some cases.…”
mentioning
confidence: 99%
“…Lesions smaller than 6 cm in diameter characteristically demonstrate a well demarcated, homogeneous, hyperechoic ultrasonographic pattern that may establish the diagnosis in 80% of patients. 4 Larger haemangiomas are more heterogenous, often complicated by thrombosis, calcification, or haemorrhage, and require further imaging by computed tomography (CT) scan or magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…[1-2] Many patients are asymptomatic, but in others, symptoms may vary from abdominal discomfort to life-threatening complications. [1] Women are more often affected by hepatic hemangioma,[3] and some studies have found that women exposed to exogenous estrogens, progesterone, contraceptives or hormone replacement therapy show a significant increase in the size of their tumors.…”
Section: Introductionmentioning
confidence: 99%